Ação coletiva entre assentados da reforma agraria: o grupo de mutirão no assentamento Benedito Alves Bandeira, município do Acará / Pará - MELO, Acácio Tarciso Moreira de (Universidade Federal do Pará, 2021)
This paper aims to study the collective strategies, or 'mutirão' (mutual-aid effort), developed by small farmers settled on the agrarian reform settlement called Benedito Alves Bandeira (BAB) in the municipality of Acará, Pará State. This research was carried out from June to November 2009 and in January 2010. The methodology included qualitative and quantitative approaches, the main procedures being: a literature review, structured and semi-structured interviews, observations and secondary data collecting. The results show a peculiar form of collective action, whereby a group (10% of the settlers) engaged in mutual-aid effort practices took over the association that manages the settlement as a whole. This was added by the fact that the 'mutirão' group, in practice, did not just address production-related issues, as is common in mutual-aid efforts, but also settlement-related political, economic and social actions. While many studies on land reform settlements point to the settlers' resistance to collective farming, especially promoted by the Landless Workers Movement (MST), the analyzed the experience shows the acceptance of the collective work of a group of settlers gathered around the 'mutirão' and aiming at agricultural production. The following factors that favored this type of work were identified: a) a previous preparation of leaders by the Catholic Church; b) voluntary performance of activities; c) the owner of the plot manages the 'mutirão' activities; d) the users themselves define the rules; and e) the size of the group. The experience of collective work in the three plots studied hereby also guides the actions taken by the association, whose meetings are held in rotation in the homes where the 'mutirão' is to be held. Despite the example provided by this type of practice used in the settlement since the beginning of its creation, there is resistance both inside and outside the settlement against the association, characterized by individual interests and the quest for power of opposing sides, which involves even government agencies. This study will contribute to understanding the strategies of reciprocity that facilitate collective action among settlers in Northeastern Pará State linking two phenomena: the little probability of cooperation, according to the logic of collective action (Olson, 1965) that questions the willingness of a group to engage in common goals; and, the promotion of cooperative work through reciprocity-based structures.